2018
DOI: 10.3892/mco.2018.1624
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the stomach: A report of two cases and a review of the literature

Abstract: Primary small cell gastric carcinomas (SCGC) are rare tumors with an aggressive nature, characterized by early, widespread metastases and poor overall prognosis. SCGC shares similar clinicopathological and molecular characteristics with small cell lung carcinoma and is usually treated in a similar manner. Here, two cases of SCGC in young Caucasian male patients are presented. One patient had metastatic and the other locoregional disease. Multimodal treatment was applied in each case; the resulting survival tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…reported that 200 of 205 Chinese patients with gastric small cell cancer underwent surgical resection, which led to a median survival of 46.45 months (range 10-63 months) [15]. Therefore, surgery is considered curative in non-metastatic gastric small cell cancer [9,14-16]. Adjuvant chemotherapy was used in 136 cases, almost all of which received two to six cycles of platinum-based combination chemotherapy [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that 200 of 205 Chinese patients with gastric small cell cancer underwent surgical resection, which led to a median survival of 46.45 months (range 10-63 months) [15]. Therefore, surgery is considered curative in non-metastatic gastric small cell cancer [9,14-16]. Adjuvant chemotherapy was used in 136 cases, almost all of which received two to six cycles of platinum-based combination chemotherapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows case reports and retrospective studies found on gastric neuroendocrine tumors treated with surgery, chemotherapy, and/or radiation. In one of the cases reported by Bakogeorgos et al., a patient with a disseminated disease of gastric neuroendocrine tumor in origin was treated with radiotherapy following etoposide and cisplatin [9]. This patient was reported to be asymptomatic and in remission 20 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…МР желудка составляет 0,1-1% всех злокачественных опухолей желудка, 15-20% всех НЭО желудка и 0,1% МРВЛ [20]. Хирургическое лечение рекомендуется использовать при локорегиональных, неметастатических стадиях с обязательной адъювантной ХТ [21][22][23][24].…”
Section: обзорunclassified